ANALISIS TEMA DAN NILAI NILAI MORAL SERTA IMPLIKASINYA DALAM PENINGKATAN KARAKTER PESERTA DIDIK PADA CERPEN INSPIRASI TANPA MENGGURUI KARYA CAHYO SATRIA WIJAYA - Ni Putu Mega Arta Widiantari; I Gusti Ayu Putu Tuti Indrawati; I Nyoman Adi Susrawan (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2022)
This research is a qualitative descriptive study that aims to find out the theme, the form of moral values and their implications for improving the character of students in the Cerpen Inspirasi Tanpa Menggurui by Cahyo Satria Wijaya. Data collection is done by the method of documentation and literature. The data in this study were processed using data triangulation analysis techniques, namely, researchers used two or more theories to be pitted or combined. The steps in data analysis are (1) reading, studying and understanding, (2) selecting data and simplifying the data, (3) presenting the data, (4) verifying the data, (5) concluding the data. The results of this study show the themes contained in the Cerpen Inspirasi Tanpa Menggurui by Cahyo Satria Wijaya, the manifestation of moral values and their implications in improving the character of students. The themes found are: stories of friendship, family problems, the meaning of a sacrifice, reflections on life, life struggles, and humans with their dignity. The manifestations of these moral values include: the form of the moral values of human relations with others: the value of caring, and the value of sacrifice. The form of the moral value of human relations with oneself: the value of purity of heart, the value of honesty and the value of independence. In all processes of the policy discovery process, evidence was found that the short story Inspirasi Without Menggurui by Cahyo Satria Wijaya could be used as teaching material or as a guide in improving the character of students. In the field of education, the results of this research can be used as literature learning materials at the SMA/SMK education level and refer to the curriculum at the education unit level